2015
DOI: 10.1007/s13197-015-2112-9
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of phenolic content, antioxidant activity and senescence-related enzymes in granulated vs non-granulated juice-sacs of ‘Kinnow’ mandarin (Citrus nobilis x C. deliciosa)

Abstract: 'Kinnow' is a hybrid mandarin, developed at California (USA) but could not become successful there. However, it revolutionized citrus industry in India, Pakistan and Bangladesh. Recent reports indicate that like other citrus fruits, it also suffers from juice-sac granulation but exact cause of this malady is not known. Fully-mature 'Kinnow' fruits were harvested and observations on some physical and biochemical attributes were recorded and their relationship was established with occurrence of granulation. Abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 16 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…For this, randomly ten fruits were randomly selected and their respiration rate was determined as per method suggested by Sharma et al (2015). For determination of ethylene evolution rate, Hewlett Packard (H.P.)…”
Section: Determination Of Respiration and Ethylene Evolution Ratesmentioning
confidence: 99%
“…For this, randomly ten fruits were randomly selected and their respiration rate was determined as per method suggested by Sharma et al (2015). For determination of ethylene evolution rate, Hewlett Packard (H.P.)…”
Section: Determination Of Respiration and Ethylene Evolution Ratesmentioning
confidence: 99%
“…Comparative analysis of flavonoids indicates the presence of their maximum amount in Ponkan peel extract (35.6 mg REQ/g) and minimum amount in Kinnow peel extract (11.7 mg REQ/g). Sharma et al (2016) studied pattern of phenolic compounds with antioxidant properties in granulated and nongranulated juicy sacs of Kinnow mandarin. The resulting output of their study indicate that granulated kinnow possess low amount of phenolic compounds (4.3 mg GAE/100 ml); ascorbic acid (16.2 mg/100 ml) with antioxidant capacity (1.78 μmol Trolox/g).…”
Section: Bioactive Compoundsmentioning
confidence: 99%
“…For this purpose, cell wall thickening happens to prevent moisture loss [13]. Previous studies have also showed that polyphenol oxidase (PPO) activity and phenolic contents have a significant influence on granulation where the granulated fruits have lower PPO activity and phenolic content [27].…”
Section: Main Causes and Mechanism Of Granulationmentioning
confidence: 99%
“…Granulation was reported to cause a significant reduction at the concentrations of SSC and TA [4]. Sharma et al [27] noted that the granulated "Kinnow" mandarin fruits exhibit lower antioxidants activity and ascorbic acid content. Fruit granulation also causes a reduction in the juice content of the citrus fruits resulting in colour change (lighter) of the juice sac [12,28,31].…”
Section: Effects Of Granulation On Nutritional Ingredientmentioning
confidence: 99%